Conformational ensemble of an intrinsically flexible loop in mitochondrial import protein Tim21 studied by modeling and molecular dynamics simulations - Srivastava, Arpita; Bala, Siqin; Motomura, Hajime; Kohda, Daisuke; Tama, Florence; Miyashita, Osamu (Biochimica et biophysica acta. General subjects, 2020)
Tim21, a subunit of a highly dynamic translocase of the inner mitochondrial membrane (TIM23) complex, translocates proteins by interacting with subunits in the translocase of the outer membrane (TOM) complex and Tim23 channel in the TIM23 complex. A loop segment in Tim21, which is in close proximity of the binding site of Tim23, has different conformations in X-ray, NMR and new crystal contact-free space (CCFS) structures. MD simulations can provide information on the structure and dynamics of the loop in solution. The conformational ensemble of the loop was characterized using loop modeling and molecular dynamics (MD) simulations. MD simulations confirmed mobility of the loop. Multidimensional scaling and clustering were used to characterize the dynamic conformational ensemble of the loop. Free energy landscape showed that the CCFS crystal structure occupied a low energy region as compared to the conventional X-ray crystal structure. Analysis of crystal packing indicates that the CCFS provides larger conformational space for the motions of the loop. Our work reported the conformational ensemble of the loop in solution, which is in agreement with the structure obtained from CCFS approach. The combination of the experimental techniques and computational methods is beneficial for studying highly flexible regions of proteins. Computational methods, such as loop modeling and MD simulations, have proved to be useful for studying conformational flexibility of proteins. These methods in integration with experimental techniques such as CCFS has the potential to transform the studies on flexible regions of proteins. •Loop modeling was used to generate multiple conformations of a loop segment.•MD simulations confirmed highly dynamic nature of the flexible loop.•CCFS is a crystal contact-free space formed in designed MBP-Tim21 fusion crystals.•CCFS structure is consistent with solution conformational ensemble of the loop.•CCFS approach provides sufficient space for flexible loops to allow their motions.